اندثار الألفاظ وبعثها من جديد: اللهجة العراقية أنموذجا - الأسدي، فالح حسن كاطع Alasadi, Faleh Hasan Katea (جامعة بابل, 2015)
هذا البحث حملت فكرته مذ كنت طالبا في مرحلة الدكتوراه، حملته وهنا على وهن وأمضيت في كتابته أكثر من عامين فكان حمله وفصاله في أكثر من ثلاثين شهرا، وقد بحثت في ألفاظ كان قد نص العلماء القدامى في مصنفاتهم على موتها أو هجرها أو تركها مثل العين وجمهرة اللغة وتهذيب اللغة ومعجم المقاييس اللغة ولسان العرب والمصباح المنير والقاموس المحيط وتاج العروس وغيرها، وقد وجدت أن هذه الألفاظ قد أحييت في اللهجة العراقية خاصة، فللعراقيين ألفاظهم الخاصة بهم، قال الخليل (ت: ١٧٥ ه): ((الدشن والداجن مثله، وهو كلام عراقي ليس من كلام البادية)) [العين، مادة (دشن): ٦/ ٢٤٣]، وقال ابن دريد (ت: ٣٢١ ه): ((وقـال البغداديون: خلبيس)) [جمهرة اللغة: ٣/ 447]، وسيأتي بيان النصين، ولم يستعمل سيبويه (ت: ١٨٠ ه) عبارة (موت الألفاظ) واستعمل عبارة (استغنت العرب عن هذا بهذا)، وهو أن يستغنى بكلمة عن أخرى، وقد أكثر سيبويه من استعمالها، كما سيتضح، وأنا أسأل نفسي: لماذا تموت ألفاظ قد تتسع دلالاتها وتصلح معانيها؟ وبعد دراسة كانت الخلاصة فيها أن هذا القول ليس حقيقة علمية مطلقة، ولا يصح أن يكون حكما عاما ينطبق على جميع الألفاظ، فالاستقراء لا يؤيده، فهذه الألفاظ قد تندثر زمنا ولكنها تبعث من جديد ولو بعد قرون، وقد أثبت البحث أن العراقيين نطقوا بألفاظ نص العلماء على موتها كما سيتضح. والحق أني لم أقرأ فيما اطلعت بحثا يتناول موضوع دراستي، وقد اطلعت على الدراسة الموسومة بـ (موت الألفاظ في العربية) للدكتور عبد الرزاق بن فراج الصاعدي من المملكة العربية السعودية-وهي أطروحة دكتوراه-ولم يكن بحثي مثلا لبحثه أو صورة منه بدليل أن روافد بحثي لا تتطابق مع روافد بحثه وعباراتي لا تشبه عباراته، أما حجتي الكبرى فهي أن بحثي تناول الألفاظ التي أدعي إماتتها وهي مستعملة في اللهجة العراقيـة خاصة، ويكفي هذا العنوان أن يكون للبحث شخصيته المستقلة عن الدراسة التي أشرت إليها. This research carried the idea ever since I was a student in the doctoral stage, his campaign and here and they and I spent in writing more than two years was the campaign and weaning in more than thirty months, has looked at the words he had the text of the old scholars death or abandoned or left to the likes of Hebron and the son of Persia and Azhari and Ibn Duraid and the son of perspective and Zubaidi and others have found that these words have revived in the Iraqi dialect private, Vllaracaan Olvazam their own, said Hebron (Tel: 175 e): ((Aldshn and domesticus like him, which is the word of Iraqis not the words of the desert)) [eye, substance (launched): 6/243], Ibn Duraid: ((The Residents: Khalbas)) [population language: 3/447], and will come statement texts, was used Sibawayh phrase (the death of words) and used the phrase (dispensed with the Arabs about this this ), which is to dispense with the word for another, has more Sibawayh of use, as will be seen, and I ask myself: Why die words may accommodate significance and serve their meanings? After the study was the conclusion in which this statement is not a scientific fact absolute, and can not be a general provision applies to all terms, Valastqra not supported, these words may disappear for so but sends again, even after centuries, has research proved that the Iraqis Ntqgua wording of the text of scientists as will be seen on her death. And the right that I have not read as seen by a research paper on the subject of my study, although closely portion of the address has been briefed on the study tagged with (the death of words in Arabic), Dr. Abdul Razak bin Faraj Assa'edi of Saudi Arabia-a doctoral thesis-was not research, for example, for consideration or a copy thereof evidence that the tributaries of the research do not match with the tributaries of his research and my words do not resemble words, the major argument is that the research dealt with the terms that pretend Amataatha which is used in the private Iraqi dialect, and this title is enough to have to search for his independent study that I referred to.
لكن بحثه لا يخلو من الهنات، ومنها أنه ذكر فعل الأمر (تعال) ثم ذكر أقوال بعض العلماء ومنهم الخليل بن أحمد الفراهيدي التي نصت على موت الفعل الماضي والمضارع منه، ثم قال: ((وفي هذا نظر فقد جاء الماضي من هذا الفعل في القرآن الكريم بكثرة كقوله عز وجل: (تَعَالَى اللَّهُ عَمَّا يُشْرِكُونَ) [النمل: 63 ])) [الأطروحة: ٨٠ ]، ولم يكن الباحث موفقا في رأيه هذا فـ ( تعالى) الواردة في القرآن الكريم فعل ماض بمعنى التنزيه لا بمعنى النداء للمجيء، وهذا متفق عليه بين أئمة اللغة والتفسير، ولم أقرأ فيما اطلعت عليه رأيا يخالف ذلك فضلا عن أن لفظة (تعالى) وردت في أربعة عشر موضعا من القرآن الكريم [ينظر: المعجم المفهرس لألفاظ القرآن الكريم: ٦١١]، ولا يمكن أن يكون الخليل قد غفل عن أربع عشرة آية من القرآن الكريم، ومنها أنه حكم بموت أفعال الأمر من الأفعال الناقصة المسبوقة بـ (ما)، وكذلك حكمه أيضا بموت أفعال الأمر من أفعال المقاربة، والحق أنه لم يقل أحد بذلك وليس هناك دليل قاطع على استعمالها فضلا عن إماتتها فلا يجوز القول بالإماتة، ومنها أن روافد بحثه خلت من مصادر مهمة لعلماء عراقيين أمثال الأستاذ طه باقر والدكتور إبراهيم السامرائي وغيرهم وقد أشرت إليهم وإلى كتبهم، ومنها أيضا أنه ذكر أفعالا زعم أن كتب العلماء نصت على موتها، وقد تتبعتها فلم أجد نصا يشير إلى موتها، مثل (شع) و(سلحف) و(أخو) وغيرها، وهناك هنات أخر لا مجال لذكرها. ولعل القارئ يلاحظ استعمالي للفظ (موت الألفاظ) في بعض المواضع رغم أني فضلت استعمال (اندثار الألفاظ) بدلا منه، وذلك لأن الموت مصطلحي ليس أكثر. وجاء هذا البحث على ثلاثة مباحث، تناولت في الأول منها: موت الألفاظ بين الحقيقة والوهم، أما الثاني فقد تناولت فيه: موت الألفاظ وإحياءها عند القدماء والمحدثين، وأما الثالث فقد تحدثت فيه عن ألفاظ نص العلماء على إماتتها، وقد بعثت من جديد في لهجة العراقيين، تم ختمت البحث بطائفة من الألفاظ التي تبدو أنها هجرت على ألسنة الكثير من العرب والطبقة الخاصة من العراقيين ظنا منهم أن دلالة ألفاظها لا تليق بهم فأنفوا منها في لهجتهم وظنوا أنها غير لائقة بهم فضيقوا من دائرة مفرداتهم، ولكن هذه الألفاظ كثر دورانها على ألسنة العامة من العراقيين بالمعنى نفسه الذي ذكر في المعجمات القديمة لأئمة اللغة، والله المستعان. But his research is not without its imperfections, including that he said did it (Come) then said some scientists sayings including Hebron bin Ahmed Faraaheedi which stipulates the death of the past tense and the present tense of it, and then said: ((In this view it last came from this act in the Qur'an Karim abundance such as saying the Almighty:) God what associates ([ant: 63])) [thesis: 80], was not a researcher successful in his opinion, this P (Almighty) contained in the Koran past tense sense of transcendence does not sense the call to come, and this agreed between the imams of language and interpretation, and did not read as seen by an opinion to the contrary as well as that of the word (God) appeared in fourteen subject of the Koran [See: Concordance to the words of the Koran: 611], and can not be Hebron may overlook fourteen verse from the Koran, and which he ruled the death of the actions of command from the modal verbs unprecedented b (what), as well as his also the death of the actions of command from the actions of the approach, and the right that he did not say a so and there is no conclusive evidence of its use as well as Amataatha not permissible to say Balamath, including the tributaries of his research free of the important sources of Iraqi scientists such as Professor Taha Baqir and Dr. Ibrahim al- Samarrai and others have referred to them and to their books, and which also he mentioned acts alleged that the scientists wrote stipulates death, has Taatbatha did not find the letter refers to the death, such as (beam) and (Slhv) and (brother) and others, and there are other flaws can not be mentioned. Perhaps the reader noticed my usage of the term (the death of words) in some places even though I preferred to use (the demise of words) instead, because the death of the terms no more. The research on the three sections, dealt with in the first of them: the death of words between truth and illusion: The second dealt with the death of words and revive the ancient and modern, and the third has talked about the words of the text of the scientists on the Amataatha, was sent again in the tone of Iraqis , then search concluded a range of terms that seem to be abandoned on the tongues of many Arabs and class for Iraqis thinking that denote Olvazaa not worthy of their Vonfoa them in their dialect and they thought it was not their decent Vdicoa of their vocabulary circle, but these words much spin on public tongues Iraqis said the same in the sense that in the old Almagamat imams language, and God.
Keywords: اللهجات العراقية -- الألفاظ اللغوية -- القرآن الكريم -- التراث العربي